Designing and Implementing a Virtual Anatomic Pathology Elective During the COVID-19 Pandemic. (27th April 2021) - Hartsough, Emily M.; Arries, Cade; Amin, Khalid; Powell, Deborah
The COVID-19 pandemic transformed conventional undergraduate medical education, converting previously in-person clerkships into virtual experiences. In order to allow students to gain exposure to the field of pathology, make connections with pathologists, and provide opportunities for letters of recommendation, the authors quickly developed a Virtual Anatomic Pathology Elective at the University of Minnesota. We succeeded in developing the foundation of a Virtual Anatomic Pathology Elective that allows for the rotation to be accessible not only to our medical students but also to international medical graduates and medical students from different programs. In 1 month, we were able to create a 4-week elective that was available before the start of the 2021 residency application season. We provided students with the closest possible experience to an in-person Anatomic Pathology Elective by developing an introductory week of lectures and assignments that provided structure for the rotation, introduced the field of anatomic pathology, and demonstrated the role of pathologists in health care. Furthermore, students attended virtual resident lectures and grand rounds, participated in virtual sign-out sessions, and presented an interesting case to the faculty at the end of their rotation. The goal was ultimately to customize the curriculum to students' interests by making the rotation applicable to those applying to pathology as well as to other specialties (eg, general surgery, internal medicine, dermatology). Overall, we were able to design and implement a novel Virtual Anatomic Pathology Elective which we know can be effectively reproduced by other medical schools.